Determination of best possible correlation for gas compressibility factor to accurately predict the initial gas reserves in gas-hydrocarbon reservoirs - Al-Fatlawi, O.; Hossain, Mofazzal; Osborne, J. (Elsevier Ltd, 2017)
© 2017 Hydrogen Energy Publications LLC Gas compressibility factor or z-factor plays an important role in many engineering applications related to oil and gas exploration and production, such as gas production, gas metering, pipeline design, estimation of gas initially in place (GIIP), and ultimate recovery (UR) of gas from a reservoir. There are many z-factor correlations which are either derived from Equation of State or empirically based on certain observation through regression analysis. However, the results of the z-factor obtained from different correlations have high level of variance for the same gas sample under the same pressure and temperature. It is quite challenging to determine the most accurate correlation which provides accurate estimate for a range of pressures, temperatures, and gas compositions. This paper presents a novel method to accurately estimate GIIP of an Australian tight gas field through identification of the most appropriate z-factor correlations, which can accurately determine the z-factor and other PVT properties for a wide range of gas compositions, temperatures, and pressures. The sensitivity study results demonstrated that a single correlation cannot work acro ss the range of pressures and temperatures for a certain gas sample necessary to calculate z-factor during simulation process and/or other analysis, such as material balance and volumetric estimate.